Supplementary Instructional Materials Via Video-Clip (SIMVI): Effects On Grade 9 Students’ Conceptual Understanding and Motivation - Bebita, Darilyn Joy (Future Science / FSH-PH Publications, 2022)
The study aimed to develop, evaluate, and determine the effectiveness of recorded video-clip lessons as supplementary materials in teaching least mastered learning competencies in science among forty Grade 9 students during the School Year 2021 - 2022. The quantitative research was used in this study using the questionnaires and pretest/ posttest and LRMDS rating sheets as the data gathering instruments. The statistical methods used to treat the data were mean, standard deviation, t-test, percentage and ranking. Both the science teachers and experts evaluated the SIMVI with a grand mean of 3.97 and 3.88 respectively interpreted as strongly agree in selected criteria such as content quality, instructional quality, technical quality and technical accuracy. There was no significant difference between the evaluation of the two groups of respondents in terms of content quality, instructional quality, technical quality and technical accuracy of SIMVI with computed t values of 0.89, 1.84, 1.46 and 1.00 which are all less than the tabular t value of 2.20. It is recommended that future researchers may conduct similar study and validate the veracity of the SIMVI as to relevance, effectiveness and efficiency.